COMPARATIVE STUDY OF PHYTOCHEMICAL COMPOSITION AND IN VITRO ANTIOXIDANT ACTIVITY FROM SWEET AND SOUR POMEGRANATE EXTRACT (PUNICA GRANATUM L) - Zidane, M; Ouahrani, M. R; Laouini, S. E (university of el oued/جامعة الوادي, 2018)
In this paper, to investigate the phenolic content and in vitro antioxidant of peel extracts from sour and sweet pomegranate (Punica Granatum L). The assessment of the antioxidant capacity using 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS), DPPH, and metal chelating radical scavenging capacity assays. Furthermore, the total phenolic content measured by Folin-ciocalteu method as well conducted. The sour peel ethanolic extract was found to contain a high content of total phenolic content, for the flavonoids sweet ethanolic extract flavonoids contained the high amount. All extracts exhibited a higher antioxidant activity and the inhibitory effect of radicals scavenging activity against ABTS, DPPH, and metal chelating. The results suggest that the sour peel ethanolic extract and sweet peel ethanolic extract can be considered as a good source of natural antioxidant.
Article
Keywords: Punica Granatum L; Phenolic content; DPPH; ABTS; Peel extract.